FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PETANI PENYEMPROT PESTISIDA DI PUSKESMAS PAAL MERAH II - Nurul Hasanah; Entianopa Entianopa; Renny Listiawaty (Sekolah Tinggi Pariwisata Mataram, 2022)
Pesticides are chemical substances used to kill or control various pests. The behavior of spraying pesticides that do not use PPE will have an impact on health such as poisoning. The use of Personal Protective Equipment (PPE) by workers while working is an effort to avoid the risk of danger in the workplace. The purpose of this study was to determine factors related to the behavior of using personal protective equipment (PPE) on pesticide spraying farmers at the UKK post at Paal Merah II Health Center. This research uses quantitative research with a cross sectional approach. The sample in this study were 52 respondents. Measurement of data is done by using questionnaires and interviews with respondents. Data analysis in this study used the chi-square test. Bivariate results show that there is a relationship between knowledge and behavior in using PPE when spraying pesticides (p-value = 0.000), there is a relationship between attitudes towards behavior in using PPE when spraying pesticides (p-value = 0.000), and there is a relationship between the availability of PPE and behavior in using PPE at the time of spraying. when spraying pesticides (p-value=0.000). This study shows that there is a relationship between knowledge, attitudes, and availability of PPE on the behavior of using PPE. It is necessary to improve counseling and guidance on occupational safety and health for pesticide spraying farmers, especially regarding the importance of using complete personal protective equipment.